2017
DOI: 10.1097/md.0000000000006648
|View full text |Cite
|
Sign up to set email alerts
|

A simple scoring algorithm predicting extended-spectrum β-lactamase producers in adults with community-onset monomicrobial Enterobacteriaceae bacteremia

Abstract: The incidence of community-onset bacteremia caused by extended-spectrum-β-lactamase (ESBL) producers is increasing. The adverse effects of ESBL production on patient outcome have been recognized and this antimicrobial resistance has significant implications in the delay of appropriate therapy. However, a simple scoring algorithm that can easily, inexpensively, and accurately be applied to clinical settings was lacking. Thus, we established a predictive scoring algorithm for identifying patients at the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
2
34
2
1
Order By: Relevance
“…Our findings confirm the importance of prior intravenous antibiotic exposure as a risk factor for infection with antibiotic-resistant bacteria promoting IET (6,9). We also demonstrated that the risk factors and outcomes for IET differ according to the onset of infection.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings confirm the importance of prior intravenous antibiotic exposure as a risk factor for infection with antibiotic-resistant bacteria promoting IET (6,9). We also demonstrated that the risk factors and outcomes for IET differ according to the onset of infection.…”
Section: Discussionsupporting
confidence: 84%
“…This scoring tool created weight-based scores based on magnitude of risk with each factor, and after analysis of various scores, the authors recommended that patients with high risk of an ESBL BSI (prediction score of ≥3) or critically ill moderate-risk patients (score of 1–2) should receive an empiric carbapenem. This cutoff threshold of 3 demonstrated a negative predictive value (NPV) of 97%, and thus there was confidence that it would not lead to undertreatment in many patients [ 7 ].…”
mentioning
confidence: 99%
“…Of AROs in the community, ESBL-producers have well known adverse effects on the prognoses of bacteremic patients in the literature [35]. Clinical predictors of ESBL-producers in community-onset bacteremia, including healthcare facility residents, urinary catheter use, previous antimicrobial therapy, frequent ED visits [36], and previous hospitalization have been reported [35]. Because of the retrospective nature of the present study, some variables were di cult to assess.…”
Section: Discussionmentioning
confidence: 93%